Reflection of thermal Cs atoms grazing a polished glass surface - Anderson,A; Haroche,S; Hinds,EA; Jhe,W; Meschede,D; Moi,L (Physical Review A, 1986)
We present an experimental study which shows that a large fraction (≤ 50%) of thermal Cs atoms are nearly specularly reflected by polished glass surfaces at grazing incidence. This effect is interesting in the context of projects aimed at storing cold alkali-metal atoms in boxes. © 1986 The American Physical Society.